Applications and challenges of biomaterial mediated mRNA delivery - Huapan Fang; Qian Chen (Open Exploration Publishing Inc., 2022)
With the rapid development of gene therapy technology and the outbreak of coronavirus disease 2019 (COVID-19), messenger RNA (mRNA) therapeutics have attracted more and more attention, and the COVID-19 mRNA vaccine has been approved by the Food and Drug Administration (FDA) for emergency authorization. To improve the delivery efficiency of mRNA in vitro and in vivo, researchers have developed a variety of mRNA carriers and explored different administration routes. This review will systematically introduce the types of mRNA vectors, routes of administration, storage methods, safety of mRNA therapeutics, and the type of diseases that mRNA drugs are applied for. Finally, some suggestions are supplied on the development direction of mRNA therapeutic agents in the future.